FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN NONKEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Wenny Wenny; Elizabeth Linandi (Jurnal Bisnis dan Akuntansi, 2012)
The purpose of this research is to obtain empirical evidence about the factors which influence capital structure. Independent variables used in this research are profitability, liquidity, firm size, business risk, growth opportunity, managerial ownership, assets structure, and times interest earned to firm capital structure. The population used in this study are nonfinancial companies listed on the Indonesia Stock Exchange (IDX) that chooses for the period of 2008 to 2010 as the sample. Sample selection procedure carried out by implementing purposive sampling method. Data are analyzed using multiple regression analysis. The result of data analysis shows that profitability, assets structure, and time interest earned have influence toward firm capital structure. Whereas the other variable such as liquidity, firm size, business risk, growth opportunity, managerial ownership, have no influence toward firm capital structure.